2012
DOI: 10.1093/rheumatology/kes002
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of IL-6 family members in tendon pathology

Abstract: Objectives. Histological examination of pathological tendon generally does not reveal signs of inflammation. However, the inflammatory cytokine IL-6 has been shown to be expressed in ruptured rotator cuff tendon. The aim of this study was to investigate the expression of IL-6 family members in painful posterior tibialis tendon (PTT) and in painful and ruptured Achilles tendon (AT) compared with normal tendon.Methods. AT samples were obtained from cadavers (normal) or from patients undergoing surgical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 22 publications
7
112
3
Order By: Relevance
“…Interestingly, pro/antiinflammatory IL-6 expression showed no significant change by 2 d but significantly reduced by 1 wk after surgery with CTGF delivery. The temporal expression pattern of IL-6 by CTGF delivery, which is different from our in vitro outcome, is likely associated with the pro-and anti-inflammatory properties of IL-6 that are differently exhibited depending on healing phases and local inflammatory environment (41,42). Similar to IL-6, the CTGFinduced MMP-3 expression was different in between in vitro and in vivo tendon healing.…”
Section: Discussioncontrasting
confidence: 77%
“…Interestingly, pro/antiinflammatory IL-6 expression showed no significant change by 2 d but significantly reduced by 1 wk after surgery with CTGF delivery. The temporal expression pattern of IL-6 by CTGF delivery, which is different from our in vitro outcome, is likely associated with the pro-and anti-inflammatory properties of IL-6 that are differently exhibited depending on healing phases and local inflammatory environment (41,42). Similar to IL-6, the CTGFinduced MMP-3 expression was different in between in vitro and in vivo tendon healing.…”
Section: Discussioncontrasting
confidence: 77%
“…Inflammatory genes, including VEGF, COX-2, IL-6, IL-6R and COL1A1, are upregulated in painful and particularly in ruptured Achilles tendons in humans [21]. Remarkably, our data showed that PRP had potential to downregulate COL1A1, VEGF, COX-2, IL-6, and IL-6R.…”
Section: Discussionsupporting
confidence: 49%
“…We have previously shown that almost all MMP and ADAMTS enzymes are expressed in normal tendon, with different patterns of expression in normal, painful and ruptured tendon [36]. Although the pattern of metalloproteinase expression was similar in Achilles and posterior tibialis tendinopathy [36,52], there are differences in the expression of some genes that we speculate may be related to differences in mechanical loading [53].…”
Section: Introductionmentioning
confidence: 85%